সত্য মামলা আগরতলা - আলী, শওকত, ১৯৩৭-
Autobiographical reminiscences of an army official about Sheikh Mujibur Rahman, 1922-1975, first president of Bangladesh and his involvement in a political conspiracy case, conducted in 1968.